Anatomical variations of donor portal vein in right lobe living donor liver transplantation: the safe use of variant portal veins. (15th October 2013) - Guler, Necdet; Dayangac, Murat; Yaprak, Onur; Akyildiz, Murat; Gunay, Yusuf; Taskesen, Fatih; Tabandeh, Babek; Bulutcu, Fisun; Yuzer, Yildiray; Tokat, Yaman
Abstract In right lobe (RL) living donor liver transplantation (LDLT), portal vein (PV) variations are of immense clinical significance. In this study, we describe in detail our PV reconstruction techniques in RL grafts with variant PV anatomy and evaluate the impact of accompanying biliary variations on the recipient outcomes. In a total of 386 RL LDLTs performed between July 2004 and July 2012, the clinical data on 52 (13%) transplants using RL grafts with variant PV anatomy were retrospectively analyzed. Portal vein anatomy was classified as type 2 in 20 patients, type 3 in 24 patients, and type 4 in eight patients. The PV reconstruction techniques utilized included back‐wall plasty (n = 21), back‐wall plasty with saphenous vein graft interposition (n = 6), saphenous vein graft interposition (n = 5), cryopreserved iliac vein Y‐graft interposition (n = 6), and quiltplasty (n = 3). There was no donor mortality. In a median follow‐up of 29 months, none of the recipients had vascular complications. Anomalous PV anatomy was associated with a high (54%) incidence of biliary variations; however, these variations did not result in increased biliary complication rate. Overall, the 1‐ and 3‐year patient survival rates of recipients were 91% and 81%, respectively. Vascular and biliary variations in RL grafts render LDLT technically more challenging. By employing appropriate reconstruction techniques, it is possible to successfully use RL grafts with PV variations without endangering recipient and donor safety.